بين المعتزلة والاعتزالية الجديدة: الاعتزالية الجديدة والتأريخ لعلم الكلام عند المسلمين - Hamdan Maghribi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This paper aims to describe the important roles of mutazilite and neo mutazilite in the development of theological science. Mutazilite is the theological stream in Islam flourished at the end of the Umayya dynasty, then spread widely during the Abbasid dynasty. In studying this, researchers use qualitative research a descriptive account of the history of the flow of mutazilite from time to time and its reform efforts. As for the results of this study, First, Mutazilite is a stream of well-known figures in debate and a powerful analyst in Islamic theological studies compared to their counterparts, the definition of this stream is that they are really rigid in combining reason and revelation in debate their theology. Second, there is a reconstruction of the mutazilite flow by the new name rationalist-modernist. This mindset is also reinforced with rationalist-materialist Western thought, they tried to disassemble the framework interpretation of revelation is based on the rationale of rational analysis, and it is refined to the preacher as the classical mutazilite did. Then strengthen it with the arguments text. Third, the most important thoughts of the neo mutazilite were the effort to revise the laws of the Shari'a that exist in the Qur'an and the Sunnah.